HUBUNGAN DERAJAT KEPRIBADIAN INTROVERT DENGAN SINDROMA PRAMENSTRUASI - Bestari, Rochmadina Suci (Biomedika, 2011)
Introvert people tend to have distress. Psicosomatic manifestation from distress on women can be appeared as premenstrual syndrome. The aim of this study is to know the correlation between social introversion stage and premenstrual syndrome. This study is an analitic observasional study with cross sectional approach, which was held on November 2006 on Medical Faculty UNS Solo. Samples were taken by purposive sampling with restriction on new university studentsclass 2006 Medical Faculty of UNS. The requirements are : (1) on premenstrual or menstrual phase, and (2) does not have reproduction organ disease. Subject  ?  lled (1) Kuesioner Riwayat Menstruasi dan Ginekologi (Gynecology and Menstrual History Questionair) to know subject?s menstrual cycle, (2) Kuesioner Skala L-MMPI (L-MMPI Scale Questionair) to state honesty in answering questions given, (3) Kuesioner Sindroma Pramenstruasi (Premenstrual Syndrome Questionair) consisted of pramenstrual syndrome?s aspects, (4) Kuesioner Skala-0 MMPI (MMPI 0-Scale Questionair) to state social introversion stage. It?s obtained 42 subjects data. Social introversion stage (SI) and premenstrual syndrome (PMS) data were then analyzed with (1) Normality test by Shapiro Wilk, and (2) Hypothetic test by Pearson correlation used SPSS 11.0 for Windows computer program.Results of this study are (1) Premenstrual subjects are bigger amount than non-premenstrual subjects (88,1% vs 11,9%), (2) there is signi?  cant positive correlation between social introversion stage and premenstrual syndrome with strong correlation (r=0,551; P<0,05). The conclusion of this study is there is signi?  cant positive correlation between social introversion stage and premenstrual syndrome.Keywords: Social introversion, premenstrual syndrome